Iliocapsularis: An exploration of the muscle and its omission in education. (14th April 2022) - Breckling, Abbey C. M.; Katrikh, Aaron Z.; Jones, Michael W.; Ferrigno, Christopher
Abstract: Anterior hip joint musculature is classically characterized to include iliacus, psoas major, rectus femoris, and sartorius muscles. A lesser‐known muscle, iliocapsularis muscle (ICm), has made infrequent appearances in the literature for the last 70 years, but potentially has important functional and clinical value. The purpose of this study is to review the historical prevalence of the ICm in peer‐reviewed literature (PRL), further explore the prevalence of the muscle in current anatomical textbooks (ATBs), characterize the muscle with a new series of dissections, assess the muscle's perceived importance to clinicians and educators, and comment on the possible functional significance of the muscle. The ICm was mentioned in 28 peer‐reviewed articles and the muscle was present in 518 of 521 (99%) dissected hips in 13 publications which assessed prevalence. In an audit of 30 recently published ATBs, three texts mentioned the ICm. In 28 anterior hip dissections performed in the current study, the muscle was present in all hips. Anatomy educators were surveyed to determine if the ICm was presently taught in their curricula, and clinicians of various specialties were surveyed regarding their perceptions of the ICm and its clinical relevance. The ICm inclusivity within anatomical curricula from educators reported 8.5%, while 4% of clinicians reported trainees should have an educational background of the ICm. This study confirms that while the ICm is present within PRL, and is ubiquitous amongst human‐donor dissection, the ICm is not mentioned in most ATBs and is absent in the vast majority of anatomical curricula. Lack of inclusion in curricula may lead to a perceived insignificance to currently practicing clinicians despite the potential functional importance at the hip. This discordance suggests that the ICm should be included in ATBs and anatomical curricula so that future clinicians can consider the ICm when evaluating and treating patients. Abstract : Since 1950, the Iliocapsularis was mentioned in 28 peer‐reviewed articles and found in 99% of dissected hips. In our 28 hip dissections, the iliocapsularis muscle (ICm) was present in all hips. Despite the ubiquity of this muscle, only 10% of anatomical textbooks (ATBs) include the ICm, and the muscle's potential functional importance is recognized by very few anatomy educators (8.5%) and clinicians (4%) ATBs. This study confirms that while the ICm is present within PRL and in our human‐donor dissections, the ICm is infrequently mentioned in most ATBs and is absent in the vast majority of anatomical curricula.